2010
DOI: 10.1063/1.3428477
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-sensitive piezophotovoltaic effects in ferroelectric nanocylinders

Abstract: Photocurrent system of the ferroelectric nanocylinder ͑FNC͒, including nanodisks, nanorods, and nanowires, sandwiched between metal electrodes with the short-circuit boundary conditions has been designed and investigated. Taking into account the polarization charge screening in the electrodes and near-surface inhomogeneous polarization distribution, a theoretical model for investigating the photoinduced current of the FNC under the illumination of light was established. Our results show that the photocurrent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…The intrinsic surface stress can induce ferroelectricity, ferromagnetism and increase corresponding phase transition temperatures in conventional ferroelectrics and quantum paraelectric nanorods, nanowires [15,16,17,18,19] and binary oxides [20].The surface stress is inversely proportional to the surface curvature radius and directly proportional to the surface stress tensor (similar to Laplace surface tension). Thus, the intrinsic surface stress should depend both on the growth conditions and the surface termination morphology [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic surface stress can induce ferroelectricity, ferromagnetism and increase corresponding phase transition temperatures in conventional ferroelectrics and quantum paraelectric nanorods, nanowires [15,16,17,18,19] and binary oxides [20].The surface stress is inversely proportional to the surface curvature radius and directly proportional to the surface stress tensor (similar to Laplace surface tension). Thus, the intrinsic surface stress should depend both on the growth conditions and the surface termination morphology [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The continuum media theory was successfully used for the analysis of elastic properties of metallic, semiconductor, dielectric or polymeric nanowires and nanotubes [31,32,33,34,35,36,37] and the piezoelectric response [38]. For nanosized ferroics, the applicability of the continuous media phenomenological theory is corroborated by the fact that the critical sizes (~2-10 lattice constants) of the appearance of long-range order calculated from atomistic [ 39 , 40 ] and phenomenological theories [17,18,19] are in good agreement with each other [37,41,42,43,44] as well as with experimental results [45]. Generally, the long-range order appears for sizes larger than the critical sizes (details can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the intrinsic surface stress can induce ferroelectricity, ferromagnetism and increase corresponding phase transition temperatures in conventional and quantum paraelectric nanorods and nanowires [11,12,13,14,15]. These facts motivated us to explore the possibility of inducing simultaneous ferroelectricity and ferromagnetism in EuTiO 3…”
Section: Motivation Of Our Studymentioning
confidence: 99%
“…Under the absence of external electric field, the thermodynamic energy of a FNC should contain the contributions of the gradient, interface, surface, and depolarization field energies. [4][5][6][7][8][9][10][11][12][13][14][15] The gradient energy density is given by DG grad ¼ 1=2D ij P i;j P i;j , where D ij are the gradient coefficients and @P i =@x j are expressed by P i;j . 13,15 The top and bottom interface energy and sidewall surface energy approximately acquire the forms as…”
mentioning
confidence: 99%